2012
DOI: 10.1177/0011000012459365
|View full text |Cite
|
Sign up to set email alerts
|

Stigma for Seeking Therapy

Abstract: The current study examined the associations among clients' perceptions of self-and social stigma for seeking help, session outcomes, and working alliance. Ninety-one clients were treated by 26 therapists, at a large university counseling center. All clients were currently in therapy. We expected that clients' perceptions of self-and social stigma would be negatively associated with session outcomes and working alliance, after controlling for number of sessions, psychological well-being, and client and therapis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Our findings replicate and extend prior research (Deres et al, 2020;Owen et al, 2013;Wade et al, 2011) by demonstrating that the self-stigma associated with seeking psychological help is related to worsened perceptions of the therapist-client working alliance. However, they are inconsistent with those reported by Kendra et al (2014), who found that within-person increases in selfstigma were associated with a stronger working alliance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings replicate and extend prior research (Deres et al, 2020;Owen et al, 2013;Wade et al, 2011) by demonstrating that the self-stigma associated with seeking psychological help is related to worsened perceptions of the therapist-client working alliance. However, they are inconsistent with those reported by Kendra et al (2014), who found that within-person increases in selfstigma were associated with a stronger working alliance.…”
Section: Discussionsupporting
confidence: 87%
“…First, Wade et al (2011) reported a significantly negative association among 263 college students receiving one session of group counseling when self-stigma was measured after session; presession levels of self-stigma were negatively but not significantly associated with alliance ratings. Second, Owen et al (2013) found that higher self-stigma was associated with lower ratings of the alliance in a sample of 91 college students receiving individual psychotherapy. Most recently, Seidman et al (2022) found a negative but not significant relationship among a sample of 138 college students attending a one-time group therapy session.…”
mentioning
confidence: 95%
“…Identities provide a window into the client’s values, beliefs, and potential consequences of nonconformance. For example, in many communities, therapy is not an ideal way to address problems, and going to therapy is stigmatizing (Owen, Thomas, & Rodolfa, 2013). Collaborating to understand the client’s illness narrative can enhance treatment outcomes with clients from marginalized groups (Benish, Quintana, & Wampold, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Further, this study allows those who have succeeded at long-term, satisfying relationships to pass on their advice and words of wisdom to the rest of the world in terms of what has been important and how difficult times were handled. Stigma around issues within relationships and seeking therapeutic help exists in our world (Owen et al, 2012), and many couples resist exposing marital imperfection, though support is known to provide healing and remediation. Soon, the last of the generations who married "for good," without fear or consideration of an overwhelming divorce rate, will be gone.…”
Section: Purposementioning
confidence: 99%